Structural Variations of Vaginal and Endometrial Microbiota: Hints on Female Infertility - Riganelli, Lucia; Iebba, Valerio; Piccioni, Mariagrazia; Illuminati, Isabella; Bonfiglio, Giulia; Neroni, Bruna; Calvo, Ludovica; Gagliardi, Antonella; Levrero, Massimo; Merlino, Lucia; Mariani, Marianna; Capri, Oriana; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Microbiota has been described colonizing all human districts in communication with the external environment, including urogenital tract. The bacteriota colonizing the vaginal district has been established, and partially related to obstetric outcome; while the uterine microbiota, considered a sterile district for years, is now subjected to deeper studies and discussion. A correct characterization of the microbiota composition in the reproductive tract (RT), in asymptomatic and infertile women, could define a specific RT microbiota associable to implantation failure, helping us to better understand the reason why of implantation failure. In this study, thirty-four female undergoing personalized hormonal stimulation were recruited and the biological samples of each patient, vaginal fluid and endometrial biopsy, were taken immediately prior to the oocyte-pick up and subject to sequencing. Subsequently the women were divided according to the outcome of fertilization. The 16s rRNA V4-V5 region sequencing analysis revealed a significant difference between vaginal and endometrium microbiome. The vaginal microbiota of pregnant women confirmed the literature data, exhibiting a lactobacilli-dominant habitat, compared to non-pregnant cases, while the endometrium bacterial colonization is characterized by a polymicrobial ecosystem where Lactobacilli were found only in the group that fails the in vitro fertilization. Overall these results could improve the notions concerning the relationship between vaginal/endometrial microbiome and reproductive success.